2021
DOI: 10.24071/uc.v2i2.3438
|View full text |Cite
|
Sign up to set email alerts
|

English Education Master Students’ Perceptions on Their Self-Efficacy in Efl Speaking Learning Contexts

Abstract: Self-efficacy should be fully integrated as one of the mainstays assisting multiverse EFL academicians to achieve greater speaking learning achievements, improve their actual communicative competencies, and justify their misconceptions of L2 speaking learning enterprises. Corresponding with these 3 aforementioned advantages, the full activation of robust self-efficacy will potentially allow EFL academicians to show greater effortful actions, resilience, motivation, and commitment to relentlessly forge their L2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Desire indicates how much the learner wants to become proficient in language, and affect illustrates the learner's emotional reactions with regard to language study (Gadner, 2003). Furthermore, Jaya (2017)…”
Section: Esteem Journal Of English Study Programme P-issn 2622-9323 E...mentioning
confidence: 99%
“…Desire indicates how much the learner wants to become proficient in language, and affect illustrates the learner's emotional reactions with regard to language study (Gadner, 2003). Furthermore, Jaya (2017)…”
Section: Esteem Journal Of English Study Programme P-issn 2622-9323 E...mentioning
confidence: 99%
“…Martasari and Ngadiman (2021) confirmed that with the terrific development of spiritual quotient, Indonesian university EFL learners have progressively transformed into more competent, strategic, and adaptable L2 speakers as they truly discover the true meaning of speaking learning obstacles they are facing currently. In another study, Wijaya (2021) strongly advocated for Indonesian university EFL teachers to continuously promote more supportive speaking learning environments where learners' selfefficacy can thrive better impacting their further speaking efforts and commitment made to achieve more satisfying speaking learning outcomes. In the last study, Wijaya and Mbato (2020) highly recommended that Indonesian EFL educationalists impart more constructive feedback and improve learners' self-beliefs toward their speaking competencies to gradually transfigure them into more competent and confident L2 speakers.…”
Section: Introductionmentioning
confidence: 99%